Short stature in children and adolescence. Causes, diagnosis and treatment. - Hussimy Marchena Morera; Alina Ester González Hermida; Jorge Luis Irizar Hernández; Greyci Cuervo-Arango Bernia; Inés Martínez Fernández; Alberto Roteta Dorado (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Growth is a biological and dynamic process that begins with fecundation and ends at the final stage of adolescence. Its development is complex and different factors intervene in it. Short stature is the most frequent growth disorder in the daily medical practice; furthermore, it is the entity that produces concern and dissent in the patient and his/her relatives. To recognize and to treat early this growth and development altered in our children and adolescence permits us to adopt diagnosis strategies and treatment that favor his/her recovery. A revision was performed with the aim to expose tools which permit health professionals to identify a patient with this disorder at early stage, and to develop behaviors for its correction in order to achieve a better life quality in pediatric patients.